An Analysis of the quantitative impact of climate change on national level economic growth: a Kenyan case study - Mbotela, Immanuel Malombe (Strathmore University, 2018)
The issue of climate change has been a growing interest in recent times for a number of reasons. Chief among them is because the economic landscape of most if not all African countries is dependent on the dynamics of climate change. Key sectors of the economy such as agriculture, forestry, energy, coastal and water resources are highly susceptible to climate change. That being the case, this paper seeks to analyze the empirical linkage between economic growth and climate change in Kenya from a quantitative point of view. Using data from two climate variables, temperature and precipitation, and employing time series analysis techniques, the paper tries to estimate both the short-run and long-run effects of climate change on growth. The paper establishes that an increase in temperature significantly reduces economic performance in Kenya. This takes the form of reducing agricultural output, industrial output, and aggregate investment, and increasing political instability. Some policy options have arisen from this study all in all. First and most importantly, mainstreaming climate change adaptation into National Development Strategy and budgets could promote proactive engagement on the formulation and implementation of climate change adaptation strategy. Second, the potential of regional or multiple countries approach to climate change adaptation is high due to possibility of economies of scale.
A Research project Submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Science in Financial Economics at Strathmore University
Keywords: Climate change; Economic growth; National development